PROFIL KOMUNIKASI MATEMATIS TULIS MAHASISWA TAHUN PERTAMA PERKULIAHAN DALAM PEMECAHAN MASALAH DIFFERENSIAL - Emanuel, Endrayana Putut Laksminto; Soewardini, Herfa Maulina Dewi (Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to describe the mathematical communication profile of first year students studying differential material. The research method begins with preparation, data collection, transcription and analysis. A total of 10 students were given math problem sheets, containing contextual story problems consisting of one number regarding differentials. A student was selected as a research subject based on Polya indicators and was interviewed in a semi-structured and in-depth manner to dig up further information and then analyzed using a cognitive lens. The research results show that the research subjects can solve mathematical problems well. The subject can communicate ordinary sentences well into mathematical sentences. The components of words use, visual mediators, narratives, and routines show that students' written mathematical communication skills are very good in solving differential problems.